Comparison of the strategies of expression of five tymovirus RNAs by in vitro translation studies - Kadaré, Gress; Drugeon, Gabrièle; Savithri, H. S.; Haenni, Anne-Lise (Journal of General Virology, 1992)
Total nucleotide sequencing of the RNA genome of various tymoviruses has demonstrated that the overall genome organization of these viruses is identical. Furthermore, the strategies of expression of the turnip yellow mosaic virus (TYMV) genome have been established by in vitro translation studies; these include the synthesis of a subgenomic RNA, the utilization of overlapping open reading frames (ORFs) and maturation of a polyprotein. In the experiments described here, the strategies of expression of other tymovirus (eggplant mosaic virus, ononis yellow mosaic virus, belladonna mottle virus and physalis mottle virus) genomes have been compared to those used by the TYMV genome, in particular to determine whether these tymoviruses also resort to the expression of overlapping ORFs and maturation of a polyprotein.